An Illustrative Case of Vein of Labbe Thrombosis Presented as a Glioma - Malikov, Azad; Saylak, Fatma Betul; Ertugrul, Yavuz; Ocal, Ozgur; Daglioglu, Ergun (Asian Journal of Neurosurgery, 2023)
Cerebral vein thrombosis is a unique and rare type of cerebrovascular disease. The main challenge in identifying cerebral vein thrombosis is the presence of vague signs and symptoms that can resemble a variety of other intracranial pathologies. Our goal is to present the unique case of a young patient whose MRI scan revealed an abnormally enhancing tumor-like brain lesion that was heterogeneous in intensity and whose intraoperative view and histopathological findings were consistent with the vein of Labbe thrombosis, with ipsilateral transverse and sigmoid sinus involvement.
Keywords: cerebral vein thrombosis; vein of Labbe thrombosis; malignant glioma; magnetic resonance venography; cortical vein thrombosis